White House Recovery Month focuses on 'all Americans'. Issue 35 (10th September 2021) - Knopf, Alison
Abstract : The White House recognized September 2021 as National Recovery Month in a Sept. 2 proclamation calling for "making treatment and recovery support services accessible to all Americans."